2006
DOI: 10.1074/jbc.m603403200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Binding Motif in Pyrococcus furiosus DNA Ligase for the Functional Interaction with Proliferating Cell Nuclear Antigen

Abstract: DNA ligase is an essential enzyme for all organisms and catalyzes a nick-joining reaction in the final step of the DNA replication, repair, and recombination processes. Herein, we show the physical and functional interaction between DNA ligase and proliferating cell nuclear antigen (PCNA) from the hyperthermophilic Euryarchaea Pyrococcus furiosus. The stimulatory effect of P. furiosus PCNA on the enzyme activity of P. furiosus DNA ligase was observed not at low ionic strength, but at a high salt concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…It is not clear why the stimulation effect of PCNA on the activity is relatively low at this stage; however, the effect is the same as the case of human UNG2 and PCNA, as reported earlier (16). In our previous study of PfuLig-PfuPCNA interaction, stimulation effect of PCNA on the ligation reaction was especially distinct at high salt reaction conditions, which are more similar to the physiological condition in the P. furiosus cells (35). In the case of PfuUDG, however, the glycosylase activity was drastically decreased at high salt concentrations (over 0.3 M KCl or potassium glutamate) both in the presence and absence of PfuPCNA (data not shown).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…It is not clear why the stimulation effect of PCNA on the activity is relatively low at this stage; however, the effect is the same as the case of human UNG2 and PCNA, as reported earlier (16). In our previous study of PfuLig-PfuPCNA interaction, stimulation effect of PCNA on the ligation reaction was especially distinct at high salt reaction conditions, which are more similar to the physiological condition in the P. furiosus cells (35). In the case of PfuUDG, however, the glycosylase activity was drastically decreased at high salt concentrations (over 0.3 M KCl or potassium glutamate) both in the presence and absence of PfuPCNA (data not shown).…”
Section: Resultsmentioning
confidence: 69%
“…The uracil excision efficiency is plotted as a function of the enzyme concentration. Ϫ7 M) and the PfuPolBPfuPCNA interaction (9.9 ϫ 10 Ϫ8 M) determined by our SPR analysis (35,36). These observations suggested that PfuUDG can interact with PfuPCNA via an unidentified binding motif.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The hLigI protein also bears a PIP-box in the N-terminal domain (11,12), whereas the corresponding domain is missing in archaeal DNA ligases. Recently, a functional PCNA binding motif of PfuLig, -QKSFF-, was found in a loop within the middle of the DBD, rather than the terminus of the enzyme (13).…”
mentioning
confidence: 99%
“…However, no typical motif sequence was found in either the N or C terminus of the peptide chain, where the PIP motif usually exists in many PCNA-binding proteins. Therefore, we predicted that the PCNA-binding site of TkoHef is located in the IDR, because PCNA-binding sites also exist in structurally flexible areas, such as looped-out regions, when present in the internal region of a peptide chain (38,40). We subjected TkoHef⌬ID to the same SPR analysis.…”
Section: Prediction Of the Idrs In The Hef/fancm Proteins-thementioning
confidence: 99%